Performing Postfeminism: Escaping Identity Politics? - Anderson, Heather (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
Examining works by three artists, this article discusses whether their sensationalist strategies and transgressions reflect a postfeminist misrecognition of privilege and evasion of identity politics – or a third-wave feminist analysis of potential complicity in the very systems under critique.